Citra Perempuan dalam Memoar Imperfect karya Meira Anastasia - Ardanela, Ardanela; Hayati, Yenni (Universitas Negeri Padang, 2024)
This study was created with the aims to describe: First, to describe the physical image of women in the memoir Imperfect by Meira Anastasia. Second, the psychological image of women in the memoir Imperfect by Meira Anastasia. Third, the image of women in their relationship with family in the memoir Imperfect by Meira Anastasia, and fourth, the image of women in their relationship with society in the memoir Imperfect by Meira Anastasia. This type of research is literary research using a mimetic approach. The data source in this research is the memoir Imperfect by Meira Anastasia. Data collection techniques in this research were carried out by reading, marking events and taking inventory of the data found. The results of this research are. First, the physical image of women which consists of a pot belly, fat body and breast shape. Second, the psychological image of women in the form of a sense of self-acceptance towards things around them, love and existence in the environment. Third, social image in relation to the family consisting of mother, wife, children and younger siblings. And fourth, the social image of women in their relationship with society, such as friendship, between people, their relationship with men, and as society's idol.